Between the gangster and the country gentleman: Male fashion during the volatile 1990s. Issue 1 (1st September 2019) - Goscilo, Helena
Official de-Sovietization during the chaotic 1990s ushered in 'The New' – ostensibly, a new sociopolitical and economic order, a new business vocabulary, the new word 'rossiiane' for Russian citizens, the New Russians and the new genre of male fashion. Much of the new, in fact, recuperated the pre-Soviet old, including appropriation of western styles in sundry walks of life. Within male fashion, sartorial choice signalled allegiance to the 'new' order, financial and social status, individualism or membership in various collectives. Glossies targeting a male readership served as both primers and advertisements for men intent on forging an identity expressed in sartorial choices derived from such western modes as grunge, pop, Mafia, British rural garb and youth-eclectic 'casual'. For better and worse, that plethora reflected the seemingly endless options for the country during the Yeltsin era.